8.20 PROSPECTS FOR THE DEVELOPMENT OF THE TRANSPORT SECTOR OF UZBEKISTAN IN THE CONDITIONS OF THE CORONAVIRUS PANDEMIC - Sobirov Azizbek Akbarovich (Innovative technologies in construction Scientific Journal, 2024)
Быстрое распространение коронавирусной инфекции по миру привело к развитию глобального кризиса в области здравоохранения, перегрузке национальных систем здравоохранения и серьезным экономическим последствиям. Значительный аспект мер по предотвращению заражения в Узбекистане, в частности, радикальное ограничение транспортной деятельности и поиск путей выхода из кризиса, стимулировал разработку инновационных решений, более безопасных, экологически чистых и эффективных. Ключевые слова: Транспорт, эффективность, пандемии коронавируса, товары и услуги, кризис, инновации, правила, мировой опыт, окружающая среда, цифровизация, инфраструктура, экология, глобальный. Аnnotation: The rapid spread of coronavirus infection around the world has led to the development of a global health crisis, an overload of national health systems and serious economic consequences. A significant aspect of measures to prevent infection in Uzbekistan, in particular, the radical restriction of transport activities and the search for ways out of the crisis, stimulated the development of innovative solutions that are safer, cleaner and more efficient. Keywords: Transport, efficiency, coronavirus pandemics, goods and services, crisis, innovation, rules, world experience, environment, digitalization, infrastructure, ecology, global. The situation of the coronavirus pandemic has greatly affected the development and prospects of the transportation industry. A drop in demand for goods and services and a high risk of contagion have led to a sharp and unprecedented decline in the volume of transport services around the world. The pandemic situation has clearly shown the consequences of inaction in almost all aspects of human life and the global economy of transportation. Prime Minister of the Republic of Uzbekistan A. Aripov Tashkent City, May 19, 2020, No. 295 of the Cabinet of Ministers, May 19, 2020, No. 295, in accordance with Annex 1, on the Highway Committee under the Ministry of Transport of the Republic of Uzbekistan: General rules; 2. The main tasks and functions of the committee; Rights and responsibility of the Committee; The main functional tasks of the committee leadership; Responsibility of the committee leadership; Organization of committee activities; The committee is structural of the central apparatus of the Ministry of Transport divisions, its regional offices, as well as a departmental member procedure of cooperation with organizations; Advisory, advisory and expert bodies of the Committee; Criteria for evaluating the effectiveness and efficiency of the committee's activity and work indicators; Funding and material and technical support of the committee's activities, pay for the work of its employees and financially encourage them; The main goals of sustainable mobility have been developed within the framework of the final regulations. Each of these goals overlaps with the Sustainable Development Goals and the targets set within them. A study of the consequences of the pandemic has shown a significant impact on overall usage, that is, in terms of supply and demand for transport services. There was a collapse of the air transport market, a significant part of the world's airlines suffered losses. The number of cars on the roads has dropped dramatically due to self-isolation recommendations. Similarly, public transport ridership has also fallen to an all-time low. Subway and commuter train ridership has also declined, and many aspects of daily life have moved online, from work flow to social interactions, education, and shopping. The pandemic will undoubtedly accelerate the adoption of online tools. This prompted our country to think about how the development of the virtual environment can complement traffic flows, facilitate the use of transport services and expand their potential.